Portrait of traditional fishermen: a socio-economic study of the fishing community in Sango, Ternate, North Maluku - Agustang, Andi Tenri Pada; Hasyim, Rustam; Safitri, Yuni Andriyani; Awaru, Andi Octamaya Tenri; Nasrul, Nasrul (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
The most prominent social stratification in fishing communities is stratification based on control of the means of production. Price determination greatly influences the socio-economic conditions of fishing communities. This gap is also seen in the fishing community in Sango Village, Ternate Island District, Ternate City. The purpose of this study is to determine how the socio-economic activities of fishing communities are related to the fishing system, organization and patterns of cooperative relationships between fishermen, profit sharing and marketing patterns and distribution of fishermen's catch. This research method uses a phenomenological study approach that places the meaning of understanding or comprehension of the object itself, through interview techniques, observation, and documentation and analyzed descriptively-qualitatively. Sango Village is a portrait of the life of a traditional fishing community. Some traditional fishermen who live in Sango Village almost lost their source of income to support their families, but over time their economic activities have improved because they still rely on their livelihoods as fishermen, and until now they still exist in developing their activities. The fishing system and tools used by the fishing community in Sango Village in general are 1. Coho nyao toma jala (catching fish with nets) 2. Coho nyao se tabadiku (catching fish with bamboo) 3. Hau/Mangail (Fishing). Organization and pattern of Cooperation Relations between fishermen there are Punggawa and juragan. The conclusion is that the social and economic activities of the fishing community in Sango Village grow and develop reciprocally with socio-cultural aspects seen from the fishing system at sea.